2015
DOI: 10.4161/21645515.2014.985500
|View full text |Cite
|
Sign up to set email alerts
|

The response of hepatitis B vaccination on seronegative adults with different vaccination schedules

Abstract: y These authors equally contributed to this work. Keywords: Hepatitis B vaccine, immunization, adults, ChinaThe purpose of this study was to compare the response of hepatitis B vaccination with different vaccination schedules among seronegative adults, and to provide suitable vaccination schedules for floating and fixed population. The study included adults aged 20 to 39 y without prior history of vaccination with hepatitis B vaccine. The serum samples were collected and tested for hepatitis B surface antigen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…What’s more, the four reports regarding different vaccination schedules in adults such as 0-1-6 and 0-1-12 schedules are still controversial 13 39 47 48 . Three studies among them 13 39 47 observed no difference in seroconversion rates between these two schedules (as in these cases they were all nearly 100%), while another study 48 showed a higher seroconversion rate in individuals with the 0-1-12 schedule. Our meta analysis found no difference for seroconversion rate one month after the third injection both in 0-1-6 and 0-1-12 vaccination schedules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…What’s more, the four reports regarding different vaccination schedules in adults such as 0-1-6 and 0-1-12 schedules are still controversial 13 39 47 48 . Three studies among them 13 39 47 observed no difference in seroconversion rates between these two schedules (as in these cases they were all nearly 100%), while another study 48 showed a higher seroconversion rate in individuals with the 0-1-12 schedule. Our meta analysis found no difference for seroconversion rate one month after the third injection both in 0-1-6 and 0-1-12 vaccination schedules.…”
Section: Discussionmentioning
confidence: 99%
“…A previous meta-analysis in 2002 observed many factors influencing response to hepatitis B vaccine, especially a decrease response to recombinant HBV vaccine at higher ages11, which suggested that earlier vaccination should be prioritized for prevention at the population level. However, in the last decade, numerous emerging reports, which focused on the seroprotection rate of hepatitis B vaccine in adults12131415161718192021222324252627282930313233343536373839404142434445464748, are still inconclusive to immunize what adults are the most appropriate in order to increase the seroprotection rate. Factors influencing immunologic response to hepatitis B vaccine in adults have been inconsistently examined in existing studies.…”
mentioning
confidence: 99%
“…Setting a 0.1% incidence rate as the threshold for controlling hepatitis B in a population, a linear model of this study suggests that the target can be accomplished only when HBsAb positive rate in the adult population exceeded 56.5%. Assuming an effective rate of 88% after a three-dose HBV vaccination 35 , the 56.5% HBsAb positive rate requires a vaccine coverage rate of 64% of the adult population.…”
Section: Discussionmentioning
confidence: 99%
“…If 0.1% incidence rate is set as the target for population control of hepatitis B, the study found that this can be attained only when HBsAb-positive rate was over 56.5% in adult population. An effective rate of 88% after a three-dose HBV vaccination 35 , requires HBV vaccination of 64% of the adult population. The large sample size, prospective nature of the study and detailed baseline data permit this to be examined in a comprehensive way and we are confident that these findings may be used for targeting vaccination programs at those with greater risk for infection, thus making optimum use of resources.…”
Section: Discussionmentioning
confidence: 99%
“…44 However, in China, there are more than 230 million migrant workers who regularly move between cities and are at high risk for HBV infection. 52 For these migrant workers, the 0-, 1-, and 6-month schedule may not be appropriate because they sometimes stay in one place for a few months and then move on to their next location. Therefore, many researchers have suggested administering the third dose 2 or 3 months after the first dose and have compared the immune effect between this schedule and the normal schedule.…”
Section: Discussionmentioning
confidence: 99%